Proximate Analysis, Antioxidant Activity, and Antibacterial Activity of Fish Sausages Fortified with Bee Bread Extract - Salma Malihah Mohammad; Amirun Afiq Badrul Hisham; Nur Atifa Mustapa; Kim Wei Chan; Norhasnida Zawawi (Journal of Food Quality)
Bee bread is rich in phenolic compounds and recently has gained attention as a food additive, which provides an alternative use to synthetic preservatives. Therefore, this study aims to analyze the proximate composition and antioxidant and antibacterial activities of fish sausages fortified with Heterotrigona itama bee bread ethanolic (BBE) extract at 0.25, 0.5, and 0.75% concentrations. Incorporation of BBE in fish sausages significantly increased the carbohydrate level and lowered the moisture content. The highest phenolic and flavonoid content were observed in fish sausages with 0.75% BBE with 23.46 ± 1.60 mg GAE/g sample and 8.05 ± 0.24 mg rutin/g sample, respectively. The antioxidant activity revealed the highest DPPH scavenging activity for 0.75% BBE fish sausage compared to synthetic additive BHT. After 28 days of frozen storage, lipid oxidation activity of fish sausages with 0.75% BBE had lower thiobarbituric acid reactive substances (TBARS) value than the negative control, but similar (p>0.05) to BHT. The phenolic compounds and antioxidant activities were significantly reduced (p<0.05) after 28 days of storage. Based on the antibacterial activity, BBE was able to inhibit tested foodborne pathogens, and the addition of BBE in fish sausage showed total plate count below 6 log10 CFU/g within 6 days of frozen storage. This research demonstrated the BBE efficiency as a natural antioxidant with antibacterial properties in fish sausages.